Efficacy and Safety of 225Ac-PSMA-617-Targeted Alpha Therapy in Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Meta-Analysis - Ma, Jiao; Li, Lanying; Liao, Taiping; Gong, Weidong; Zhang, Chunyin (Frontiers in Oncology, 2022)
Objective: To conduct a meta-analysis of the efficacy and safety of 225Ac-PSMA-617 in the treatment of metastatic castration-resistant prostate cancer based on existing clinical evidence. Methods: Search for retrospective studies about 225Ac-PSMA-617 in the treatment of metastatic castration-resistant prostate cancer from establishment to July 2021 in PubMed and EMBASE. The primary endpoint was 225Ac-PSMA-617 biochemical response evaluation criteria after treatment (any prostate specific antigen [PSA] decrease and PSA decrease> 50% from baseline) to evaluate the treatment effect. Secondary endpoints included assessment of overall survival (OS), progression-free survival (PFS), molecular response, and toxicity for all studies. Two researchers conducted literature screening, data extraction and quality evaluation according to the inclusion and exclusion criteria. Use stata16.0 software for analysis, fixed-effects model for data merging and forest plots for display. Results: A total of 6 retrospective studies , including 201 patients, were included in the final analysis. The pooled proportions of patients with decreased PSA and PSA decreased by more than 50% were 87.0% (95% confidence interval, 0.820 to 0.920) and 66.1% (95% confidence interval, 0.596 to 0.726), respectively. The pooled proportions of OS and PFS were 12.5 months (95% CI: 6.2-18.8 months) and 9.1 months (95% CI: 2.6-15.7 months). The patients showing molecular responses was 54% (95% confidence interval: 25%-84%). In all studies, the most common side effect of 225 Ac-PSMA-617 TAT was xerostomia, with any degree of xerostomia occurring in 77.1% (155 out of 201), and grade III only accounted for 3.0%. The second was 30.3% (61 out of 201) anemia of any degree, and grade III accounts for 7.5% (15 out of 201). Grade III leukopenia and thrombocytopenia were 4.5% (9 out of 201) and 5.5% (11 out of 201), respectively. Only 6 (3.0%) of 201 patients had Grade III nephrotoxicity. Conclusion: 225Ac-PSMA-617 is an effective and safe treatment option for mCRPC patients, and the toxicity caused by it is relatively low. However, future randomized controlled trials and prospective trials are required in the future to judge the therapeutic effects and survival benefits compared with existing clinical treatments.